Effect of gradient temperature rolling on microstructure of initial pass of ultra-heavy plates. Issue 2 (February 2019) - Xu, Bo; Fu, Hongyuan; Zhang, Xin; Bian, Shouyuan; Yan, Ling; Li, Shengli
Abstract: In this paper, the gradient temperature rolling (GTR) method is used to establish the rolling model of the first two passes by using the deform-3D finite element software. The variation of temperature field, stress field, static recrystallization and average grain size of ultra-heavy plate slab under different conditions is systematically studied. Test result shows that the water cooling between the passes can form a temperature gradient layer (about 30mm) of a certain thickness on the surface of the rolled blank, the deformation of the core can be effectively improved during the rolling process, the static recrystallized grain size and average grain size of the surface of the rolled part are more obvious than the uniform temperature rolling; in addition, since the surface temperature of the water-cooled product is low, the amount of deformation is small, and metastable dynamic recrystallization does not occur.